Analisis Keberadaan Unsur Ribawi pada Sistem Jual Beli Shopee Paylater - Sucinta Tri Nurhayati; Embun Febryanti Panggabean; Arfi Andira Kirana; Hesty Ananta Yunas; Rizqa Amelia (Trending: Jurnal Manajemen dan Ekonomi, 2023)
Paylater is widely used in carrying out sales and purchase transactions. This research aims to analyze the existence of ribawi elements in the context of the Shopee Paylater purchase system. Shopee Paylater is a service that allows users to purchase products online and pay later with a specified interest or additional fee. In Islam, there are principles that govern financial transactions, including the concept of riba or interest. Therefore, it is important to analyze whether the Shopee Paylater purchasing system involves a ribawi element or not.